Cytoplasmic CPSF6 Regulates HIV-1 Capsid Trafficking and Infection in a Cyclophilin A-Dependent Manner - Zhou Zhong (American Society for Microbiology, 2021)
HIV is the causative agent of AIDS, which has no cure. The protein shell that encases the viral genome, the capsid, is critical for HIV replication in cells at multiple steps.